2006
DOI: 10.1681/asn.2005080799
|View full text |Cite
|
Sign up to set email alerts
|

A Pathogenetic Role for Mast Cells in Experimental Crescentic Glomerulonephritis

Abstract: Mast cells infiltrate kidneys of humans with crescentic glomerulonephritis (GN),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 45 publications
(35 reference statements)
4
35
1
Order By: Relevance
“…Increasing evidence suggests that MCs play critical roles in IgGdependent tissue-specific autoimmune diseases, including murine models of multiple sclerosis, RA, bullous pemphigoid, and glomerulonephritis (41)(42)(43)(44). In RA, circulating IgG isotype autoantibodies and immune complexes can activate synovial MCs through FcγRs (19), triggering release of inflammatory cytokines including TNF, IL-1β, and IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that MCs play critical roles in IgGdependent tissue-specific autoimmune diseases, including murine models of multiple sclerosis, RA, bullous pemphigoid, and glomerulonephritis (41)(42)(43)(44). In RA, circulating IgG isotype autoantibodies and immune complexes can activate synovial MCs through FcγRs (19), triggering release of inflammatory cytokines including TNF, IL-1β, and IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have suggested that a reduction of mast cells, or their typical enzyme chymase, increases fibrosis (52)(53)(54)(55)(56), whereas others suggest the opposite (57,58). Thus, the potential therapeutic value of mast cell manipulation in fibrosis is uncertain (23,59).…”
Section: The Role Of Immune Cellsmentioning
confidence: 99%
“…Timoshanko et al 122 demonstrated a role for mast cells in inducing functional renal injury by the mechanism of infiltrating mast cells that recruit DTH effector leukocytes. These local effects were comparable to studies showing a role for mast cells in dermal DTH.…”
Section: Role Of Mast Cells In Inflammatory and Autoimmune Kidney Dismentioning
confidence: 99%